Early years pathways to inequalities in childhood asthma? A causal mediation analysis. (30th September 2020) - Creese, H; Mason, K; Schlüter, D K; Taylor-Robinson, D; Saxena, S
Abstract: Background: Asthma affects one in five children in the United Kingdom (UK). Children in deprived areas have twice as many unplanned admissions for wheeze but mediating pathways between socioeconomic circumstances and asthma remain unclear. We aimed to quantify which early years pathways explain inequalities in childhood asthma in the UK. Methods: We analysed data on 10650 children from the Millennium Cohort Study (MCS), a nationally representative sample of the UK population. Early life socioeconomic circumstance (SEC) was measured by maternal education at birth. Our outcome was parent-reported asthma at 5 years of age categorised as none, diagnosed asthma and diagnosed asthma with wheeze symptoms in the preceding year. Mediators were grouped into perinatal characteristics (maternal BMI, breastfeeding duration, birthweight, gestation, maternal smoking and alcohol use during pregnancy), neighbourhood features (pollution, grime and environment issues, traffic volume, housing quality) and the home environment (damp/condensation, tenure, pets, tobacco smoke). We used multinomial regression to examine the total effect of SEC on childhood asthma, then adjusted for all potential mediators. Using causal mediation analysis, we will estimate the proportion mediated by blocks of mediators and the natural indirect effect (NIE) via each block of mediators. Results: Children whose mothers had no qualifications were more than twice as likely to have asthma by the age of 5 years with a wheeze episode in the preceding year compared with those whose mothers had degree-level qualifications (relative risk (RR) 2.21, 95% CI 1.44 to 3.40). After adjustment for all mediators, there was a 69% reduction to aRR 1.38 (95% CI 0.89 to 2.14). Conclusions: Perinatal characteristics and early years neighbourhood features and measures of the home environment partially contribute to inequalities in childhood asthma. Key messages: The antenatal period and early years of development are important for targeting interventions to reduce inequalities in asthma. About two-thirds of the social inequality in childhood asthma was explained by perinatal characteristics, early years neighbourhood features and the home environment.